A rare case of hepatic metastasis 20 years after surgical resection of a thymoma: A case report. (October 2021) - Dhahir Ali, Fetyan; Kuebler, Stefan; Lakenberg, Nora; Hermann, Laura; Mall, Julian; Fangmann, Josef
Abstract: Introduction: Thymoma is the most common solid, primary mediastinal tumour, accounting for 20% of mediastinal neoplasms. Malignant thymus tumours (thymomas and thymic carcinomas) metastasize primarily locally. Distant metastases, especially to liver are very rare. Presentation of case: We review the case of a 59 year-old female patient, who underwent resection of the thymus with a diagnosed type B2 thymoma 20 years ago. The patient was referred to our hospital with a newly discovered space-occupying lesion in the liver, which had been detected in a routine follow-up magnetic resonance imaging scan. Since a malignant tumour of the liver could not be excluded, a conventional left hemihepatectomy was performed. Histological examination revealed a liver metastasis of the type B2 thymoma, which had been removed 20 years ago. Clinical discussion: The case was discussed in the interdisciplinary tumour board. Based on the very long history of the primary removal of the thymoma as well as the R0 resection of the liver metastasis, a follow-up regimen with CT scans on a regular basis was recommended. Conclusions: Newly discovered lesions of the liver in patients even with a long history of a thymoma should raise the suspicion of a liver metastasis that should be surgically resected as the therapy of choice. Further, this case indicates the importance for long-term radiographic follow-up. Highlights: Thymomas are common tumours mainly found in the mediastinum. Thymic carcinoma accounts for about 25% of thymic tumours Thymic carcinomas metastasize mainly locally and rarely distally. Liver metastasis of thymic carcinoma can occur many years after resection of the primary tumour. Liver metastases of thymic carcinoma are rare.